ANALISIS ENERGI PADA PENGERINGAN PARING DI PT. ROYAL COCONUT AIRMADIDI - Yulian Sagrim; Prof. Ir. Robert Molenaar, MS, PhD; Dr. Ir. Frans Wenur, MS (Universitas Sam Ratulangi, 2020)
ABSTRACTThis study aims to identify the use of energy sources at the stage of the paring process,calculate the total energy used at the stage of the paring process and calculate the energyefficiency in this case, the efficiency of drying at the paring drying process. From the results ofthis study found the total energy used for paring drying at PT. Royal Coconut Airmadidi of22,808,070,020,500 joules. While the drying efficiency was found to be 33.2%, it means that outof 100% of the energy expended, only 33.2% was actually used in the paring drying process.Keywords: Energy Analysis, Paring Drying.